Incidence and characteristics of pseudoprogression in IDH-mutant high-grade gliomas: A POLA network study. Issue 3 (12th August 2022) - Seyve, Antoine; Dehais, Caroline; Chinot, Olivier; Djelad, Apolline; Cohen-Moyal, Elisabeth; Bronnimann, Charlotte; Gourmelon, Carole; Emery, Evelyne; Colin, Philippe; Boone, Mathieu; Vauléon, Elodie; Langlois, Olivier; et al.
Abstract: Background: Incidence and characteristics of pseudoprogression in isocitrate dehydrogenase-mutant high-grade gliomas (IDHmt HGG) remain to be specifically described. Methods: We analyzed pseudoprogression characteristics and explored the possibility of pseudoprogression misdiagnosis in IDHmt HGG patients, treated with radiotherapy (RT) (with or without chemotherapy [CT]), included in the French POLA network. Pseudoprogression was analyzed in patients with MRI available for review (reference cohort, n = 200). Pseudoprogression misdiagnosis was estimated in this cohort and in an independent cohort (control cohort, n = 543) based on progression-free survival before and after first progression. Results: In the reference cohort, 38 patients (19%) presented a pseudoprogression after a median time of 10.5 months after RT. Pseudoprogression characteristics were similar across IDHmt HGG subtypes. In most patients, it consisted of the appearance of one or several infracentimetric, asymptomatic, contrast-enhanced lesions occurring within 2 years after RT. The only factor associated with pseudoprogression occurrence was adjuvant PCV CT. Among patients considered as having a first true progression, 7 out of 41 (17%) in the reference cohort and 35 out of 203 (17%) in the control cohort were retrospectively suspected to have a misdiagnosed pseudoprogression. Patients with a misdiagnosed pseudoprogression were characterized by a time to event and an outcome similar to that of patients with a pseudoprogression but presented with larger and more symptomatic lesions. Conclusion: In patients with an IDHmt HGG, pseudoprogression occurs later than in IDH-wildtype glioblastomas and seems not only frequent but also frequently misdiagnosed. Within the first 2 years after RT, the possibility of a pseudoprogression should be carefully considered.